2016
DOI: 10.3390/toxins8080232
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolytic Fate of 3/15-Acetyldeoxynivalenol in Humans: Specific Deacetylation by the Small Intestine and Liver Revealed Using in Vitro and ex Vivo Approaches

Abstract: In addition to deoxynivalenol (DON), acetylated derivatives, i.e., 3-acetyl and 15-acetyldexynivalenol (or 3/15ADON), are present in cereals leading to exposure to these mycotoxins. Animal and human studies suggest that 3/15ADON are converted into DON after their ingestion through hydrolysis of the acetyl moiety, the site(s) of such deacetylation being still uncharacterized. We used in vitro and ex vivo approaches to study the deacetylation of 3/15ADON by enzymes and cells/tissues present on their way from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 42 publications
4
24
1
Order By: Relevance
“…The results in the present study are in agreement with findings in the literature indicating that DON3Glc and T2Glc are stable under upper GI conditions in vitro . Acetylated DON has also been found to be stable to digestive enzymes in vitro . One in vivo study in rats confirms the stability of DON3Glc in the small intestine, but authors report hydrolysis of ZEN14Glc to free ZEN as early as the stomach .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results in the present study are in agreement with findings in the literature indicating that DON3Glc and T2Glc are stable under upper GI conditions in vitro . Acetylated DON has also been found to be stable to digestive enzymes in vitro . One in vivo study in rats confirms the stability of DON3Glc in the small intestine, but authors report hydrolysis of ZEN14Glc to free ZEN as early as the stomach .…”
Section: Discussionsupporting
confidence: 93%
“…However, lower bioavailability of NIV compared to DON has been reported in broilers [38] and further studies will be required to elucidate possible differences in absorption and the potential role of efflux pumps. We found no evidence of metabolism of DON by intestinal cells, but deacetylation of acetylated DON by small intestinal preparations has been shown recently [30]. Our findings of the efficient transport of T2/HT2 demonstrate high bioavailability of these potent type-A trichothecenes.…”
Section: Discussioncontrasting
confidence: 48%
“…(c) Metabolism of D3G in pigs (Zhang et al., 2019). (d) Deacetylation of 3‐ADON and 15‐ADON in humans (Ajandouz et al., 2016)…”
Section: Toxicity Of Don and Its Modified Formsmentioning
confidence: 99%
“…Digestive enzymes, bacteria, intestinal, liver, and colon participated in the deacetylation process, and only free DON was found in the systemic blood. Once consumed, 3% and 7%, 10% and 26%, 2.6% and 0.9%, 26% and 13%, 1.7% and 0.7%, and 56% and 52% of 3‐ADON and 15‐ADON were deacetylated by pepsin, pancreatic enzymes, colonic bacteria, small intestine, colon, and liver, respectively, resulting in no acetylation forms in the whole blood circulation (Ajandouz et al., 2016).…”
Section: Toxicity Of Don and Its Modified Formsmentioning
confidence: 99%
“…Some analytical methods for the simultaneous determination of DON and its modified forms have been developed and their occurrence in food commodities have been reported [ 12 , 13 , 14 ]. Recent studies showed that these modified forms of DON were metabolized into DON in vivo, which may exert the same toxic effects as DON [ 15 , 16 ]. In 2017, the European Food Safety Agency (EFSA) evaluated the risk of DON and its modified forms and set a group-TDI for the sum of DON, 3ADON, 15ADON and D3G [ 17 ].…”
Section: Introductionmentioning
confidence: 99%